Analisis Lagu “Bulan Dikekang Malam” Dari Rossa Menggunakan Pendekatan Objektif - Leni Mastura (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
The song is a part of musical art that combines lyrical texts with melody and rhythm. Song lyrics are expressions of thoughts and feelings, crafted into messages or meanings the musician intends to convey. One song that holds deep meaning is "Bulan Dikekang Malam" (The Moon Bound by Night), performed by Rossa. This song highlights the theme of love hindered by circumstances, delivered through poetic symbolism of the moon and night. This study aims to explore the meaning embedded in the lyrics of "Bulan Dikekang Malam" using an objective approach. The method used in this research is a qualitative descriptive method. Qualitative descriptive research involves data collection techniques utilizing library studies to provide a comprehensive description of the findings (Cahya et al., 2021). The qualitative method is employed because the data aligns with actual circumstances, consisting of text that is then analyzed and interpreted objectively. After the analysis, the findings are articulated in written words and language. The steps involved include selecting the song, analyzing the lyrics, dividing the lyrics into stanzas, interpreting the lyrics using the objective approach theory, identifying signifiers and signified, and describing the findings in writing according to the data analysis results. The study reveals that the lyrics of "Bulan Dikekang Malam" convey a universal message about the struggle of love that cannot be fulfilled due to limitations. The moon symbolizes hope or love, while the night represents obstacles or restrictive situations. Through the objective approach, this meaning is thoroughly uncovered without being influenced by external contexts. This research demonstrates how the song blends lyrical aesthetics with musical harmony to create a profound emotional experience for its listeners.